2008
DOI: 10.1002/jclp.20561
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy with religious and spiritual clients: an introduction

Abstract: This invited issue of the Journal of Clinical Psychology: In Session is devoted to psychotherapy with religious and spiritual clients. After offering definitions of religion and spirituality, noting areas of potential convergence and differentiating nuances, the authors highlight the prevalence and types of spirituality among both clients and mental health professionals. They describe the historical and current context for examining approaches to psychotherapy with clients who endorse religion, experience spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…Cultural humility and religious commitment. As stated previously, clients' selfrated religious commitment can influence the degree of fidelity and trustworthiness that they ascribe to their clinicians, and studies have shown that level of religious commitment can interact with cultural humility to impact therapy (Owen et al, 2014, Worthington & Aten, 2009). For instance, Owen and colleagues (2014) found that while clinician cultural humility was positively associated with therapy outcomes in general, it was of greater importance when clients were high in religious commitment.…”
Section: Intersecting Factor Relationshipsmentioning
confidence: 97%
See 3 more Smart Citations
“…Cultural humility and religious commitment. As stated previously, clients' selfrated religious commitment can influence the degree of fidelity and trustworthiness that they ascribe to their clinicians, and studies have shown that level of religious commitment can interact with cultural humility to impact therapy (Owen et al, 2014, Worthington & Aten, 2009). For instance, Owen and colleagues (2014) found that while clinician cultural humility was positively associated with therapy outcomes in general, it was of greater importance when clients were high in religious commitment.…”
Section: Intersecting Factor Relationshipsmentioning
confidence: 97%
“…on measures of religious commitment (more than one standard deviation above average) tend to interpret life events using a religious lens, and they demonstrate greater sensitivity to the religious perspective of their clinicians (Worthington, 1988;Worthington & Aten, 2009).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…There are also several case studies applying spiritual or religious interventions from which we can learn, like Dwairy's (2009) case study of the effect of therapy with Arab-Muslim clients using culture analysis and metaphor psychotherapy. With so many spiritually oriented therapists (there are, for instance, 50,000 therapists in the American Association of Christian Therapists alone; Worthington and Aten, 2009), psychology offers many examples of forms and instruments, both for practice and research, that could be adapted for the conflict resolution field.…”
Section: Awareness and Disclosure Of Values (Lessons From Psychology)mentioning
confidence: 99%